Respuesta :

Answer:

1). a = 9.42 m

2). b = 6.37 m

3). c = 4.48 m

Step-by-step explanation:

In the figure attached,

By applying tangent rule in triangle ADE,

tan47 = [tex]\frac{h}{c}[/tex]

c = [tex]\frac{h}{\text{tan}47}[/tex]

c = [tex]\frac{4.8}{\text{tan}47}[/tex]

c = 4.476

c ≈ 4.48 m

Now we apply the same rule in triangle ACE,

tan37° = [tex]\frac{h}{b}[/tex]

b = [tex]\frac{h}{\text{tan}37}[/tex]

b = [tex]\frac{4.8}{1.0724}[/tex]

b = 6.37 m

Now apply the tangent in triangle ABE,

tan27° = [tex]\frac{h}{a}[/tex]

a = [tex]\frac{h}{\text{tan}27}[/tex]

a = [tex]\frac{4.8}{0.5095}[/tex]

a = 9.42 m

Ver imagen eudora
ACCESS MORE